2002
DOI: 10.1046/j.1468-2982.2002.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Haemochromatosis in Two Cousins with Cluster Headache

Abstract: A 60-year-old woman with secondary chronic cluster headache had increased serum ferritin and serum transferrin saturation and was homozygous for the C282Y mutation in the HFE gene, which is indicative of hereditary haemochromatosis. Treatment with venesection that normalized her iron stores led to a radical improvement of her headache complaints that had been daily for several years. Later, the headache returned to some degree in spite of normal serum ferritin levels. Her cousin, a 33-year-old man who had had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Stovner et al . described the case of a 60‐year‐old woman with hereditary haemochromatosis and chronic migraine. Therapeutic venesection was started, with removal of 500 mL of venous blood weekly for 2 months.…”
Section: Migraine and Red Blood Cellsmentioning
confidence: 99%
“…Stovner et al . described the case of a 60‐year‐old woman with hereditary haemochromatosis and chronic migraine. Therapeutic venesection was started, with removal of 500 mL of venous blood weekly for 2 months.…”
Section: Migraine and Red Blood Cellsmentioning
confidence: 99%
“…1). In humans, the CACNA1A gene is causatively linked to familial hemiplegic migraine (Ducros et al, 1999;Hans et al, 1999;Pietrobon, 2002) and may provide an intriguing explanation for the increased prevalence of severe headaches reported for people with hemochromatosis or brain iron abnormalities Stovner et al, 2002;Boes et al, 2006;Gaul et al, 2007). (Fig.…”
Section: Pathway Enrichment Analysismentioning
confidence: 99%
“…However there have been few, if any, studies of brain iron levels in large cohorts of hemochromatosis patients. While liver damage, arthritis and diabetes are the most well documented clinical consequences of hemochromatosis, some clinical and epidemiological studies have suggested possible associations with neurologic problems, including extreme fatigue (Whitlock et al, 2006;Allen et al, 2008;McLaren et al, 2008) and severe headaches Stovner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Migraine and CH may coexist in the same patients and it has been suggested that common genetic factors may play a role in the pathogenesis of both disorders 9 . Finally, a recent report described the coexistence of CH and hemochromatosis in two cousins 10 . Treatment with venesection normalized iron deposits and led to a radical improvement of CH attacks.…”
mentioning
confidence: 99%